What Are The Most Effective Management Strategies For Nonalcoholic Fatty Liver Disease Across Different Age Groups, Obesity Levels, And Metabolic Risk Profiles? : A Systematic Review - Luthfiyya Syafiqa Tahany; Sinarty Hartanto (The International Journal of Medical Science and Health Research, 2025)
Introduction: Nonalcoholic fatty liver disease (NAFLD) is a growing global health issue linked to obesity and metabolic syndrome, ranging from simple steatosis to severe conditions like cirrhosis.  Its complex pathophysiology, centered around insulin resistance, necessitates a multifaceted management approach to address its hepatic and extrahepatic consequences.  This systematic review synthesizes evidence from recent randomized controlled trials to identify the most effective management strategies across diverse patient populations. Methods: Following PRISMA guidelines, a systematic search was conducted across PubMed, Semantic Scholar, Springer, and Google Scholar.  Inclusion criteria targeted randomized controlled trials examining lifestyle, dietary, exercise, or pharmacological interventions for NAFLD, with quantifiable liver and metabolic outcomes.  Nine studies were selected for data extraction and quality assessment.  Results: The nine trials demonstrated significant improvements with various interventions.  Exercise interventions reduced intrahepatic triglycerides by up to 16%.  Dietary changes were highly effective; a "green" Mediterranean diet reduced intrahepatic fat by 38.9%, and an Indo-Mediterranean diet improved steatosis in children.  Pharmacological agents also showed promise; the combination of dapagliflozin and omega-3 carboxylic acids reduced liver fat by 21%, while resmetirom achieved reductions of 42-49%.  Mobile app-supported lifestyle interventions and intensive weight loss programs also led to significant metabolic and hepatic benefits. Discussion: The evidence confirms that tailored interventions are crucial. Exercise provides benefits independent of significant weight loss.  The superiority of specific diets, like the polyphenol-rich green Mediterranean diet, highlights the importance of dietary quality over mere caloric restriction.  Pharmacological therapies, particularly resmetirom, are emerging as powerful options for high-risk patients.  The effectiveness of interventions is modified by factors like age, comorbidities, and adherence, underscoring the need for personalized medicine. Conclusion: NAFLD is a manageable condition. Effective management is achievable through diverse, tailored pathways, including structured exercise, specific diets, intensive lifestyle programs, and targeted pharmacotherapies. A personalized, multifaceted approach that considers individual patient characteristics is essential for optimizing both liver-specific and systemic metabolic outcomes.